Taman Indoor Bonsai Pekanbaru Dengan Pendekatan Arsitektur Organik - Sabila Khalmi; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Indoor Park allows users to enjoy the beauty of nature comfortably. Bonsai as an art of miniaturized plants which always popular can filled the indoor park to become a natural tourist attraction, education for the community and commercial for gardening and bonsais in the city of Pekanbaru. Based on data collection, literature study, comparative study, and empirical study, the concept of "Grow Out" is suitable for the design. The term "Grow Out" is inspired by the shape of the bonsai roots that grow out of the pot/vase and branch off, it makes visitors want to explore the Indoor park even further. Principles of Organic Architecture such as the determination of concepts derived from nature, site alignment, the use of materials from nature, and the use of transparent materials applied in the design.Keywords: Nature, Indoor Park, Bonsai, Pekanbaru, Organic Architecture, Grow Out